2017
DOI: 10.1007/s00204-017-2140-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards a generic physiologically based kinetic model to predict in vivo uterotrophic responses in rats by reverse dosimetry of in vitro estrogenicity data

Abstract: Physiologically based kinetic (PBK) modelling-based reverse dosimetry is a promising tool for the prediction of in vivo developmental toxicity using in vitro concentration–response data. In the present study, the potential of this approach to predict the dose-dependent increase of uterus weight in rats upon exposure to estrogenic chemicals was assessed. In vitro concentration–response data of 17β-estradiol (E2) and bisphenol A (BPA) obtained in the MCF-7/BOS proliferation assay, the U2OS ER-CALUX assay and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 60 publications
2
51
0
Order By: Relevance
“…Starting point in the extrapolation are the EC 50 /IC 50 values obtained with yeast-based bioassays. Recently, Zhang et al (2018) and Fabian et al (2019) revealed that results obtained with a yeast estrogen screen (YES) provide a good prediction of the in vivo potency of BPA, after conversion of the in vitro effective concentration of this compound to equivalent oral doses in rats using PBK-based reverse dosimetry. Zhang et al (2018) even reported a better predictive value using data from the yeast bioassay than using the MCF-7/BOS proliferation or the U2OS ER-CALUX bioassays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting point in the extrapolation are the EC 50 /IC 50 values obtained with yeast-based bioassays. Recently, Zhang et al (2018) and Fabian et al (2019) revealed that results obtained with a yeast estrogen screen (YES) provide a good prediction of the in vivo potency of BPA, after conversion of the in vitro effective concentration of this compound to equivalent oral doses in rats using PBK-based reverse dosimetry. Zhang et al (2018) even reported a better predictive value using data from the yeast bioassay than using the MCF-7/BOS proliferation or the U2OS ER-CALUX bioassays.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al (2018) and Fabian et al (2019) revealed that results obtained with a yeast estrogen screen (YES) provide a good prediction of the in vivo potency of BPA, after conversion of the in vitro effective concentration of this compound to equivalent oral doses in rats using PBK-based reverse dosimetry. Zhang et al (2018) even reported a better predictive value using data from the yeast bioassay than using the MCF-7/BOS proliferation or the U2OS ER-CALUX bioassays. Though these results suggest that relevant absolute potency estimates can be made with in vitro assays like the yeast-based bioassay used in the present study, the goal of the present work was mainly to determine the in vivo relative potencies of different bisphenol analogues compared to BPA.…”
Section: Discussionmentioning
confidence: 99%
“…shown that data on in vivo toxicity can be adequately predicted by translation of in vitro concentration-response curves to in vivo dose-response curves for toxicity using this in vitro-in silico approach Louisse et al, 2010;Zhang et al, 2018). In this way in vivo dose effect levels and PoDs have been defined, for example for developmental toxicity Louisse et al, 2010;, kidney toxicity , and estrogenicity (Zhang et al, 2018).…”
Section: Pbk Modelling-based Reverse Dosimetrymentioning
confidence: 99%
“…Chemical research in toxicology 14, 101-109. Zhang, M., van Ravenzwaay, B., Fabian, E., Rietjens, I.M., Louisse, J., 2018. Towards a generic physiologically based kinetic model to predict in vivo uterotrophic responses in rats by reverse dosimetry of in vitro estrogenicity data.…”
Section: Objectives and Outline Of The Thesismentioning
confidence: 99%
See 1 more Smart Citation